Mechanical Extraction of Pili Pulp Oil: System Development, Yield Performance, and Oil Quality Analysis (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Pili (Canarium ovatum) is a tropical nut crop valued for its oil-rich pulp with applications in food, cosmetic, and pharmaceutical industries. Traditional extraction methods are labor-intensive and produce inconsistent oil quality. This study developed and evaluated a novel electrically driven mechanical extraction system specifically designed for pili pulp, incorporating optimized screw geometry and an integrated post-processing workflow. The prototype features a low-shear screw conveyor, food-grade contact materials, and inline filtration, distillation, decolorization, heating, and cooling modules. Optimal performance was achieved at 20 kg batch size, 20 rpm operating speed, and 20 minutes extraction time, producing 7.1 liters of oil (58.36% yield). Oil analysis showed desirable physical properties (specific gravity 0.89), chemical stability (peroxide value 5.4 meq/kg), and high carotenoid content (56.8 mg/100 g). Compared with manual and village-level presses (Table 5), the prototype improved yield by 4–5× and reduced extraction time by up to 75%. Economic analysis showed a 96% rate of return and 2.4-month payback period. Sensitivity analysis confirmed profitability under varying price, labor, and throughput conditions. The developed system provides a scalable and economically robust solution for standardized pili pulp oil production.